Direct Graphene‐Carbon Nanotube Composite Ink Writing All‐Solid‐State Flexible Microsupercapacitors with High Areal Energy Density. (20th February 2020) - Wang, Yaling; Zhang, Yan; Wang, Guolong; Shi, Xiaowei; Qiao, Yide; Liu, Jiamei; Liu, Heguang; Ganesh, Anandha; Li, Lei
Abstract: The advancement of miniaturized electronic devices requires the development of high‐performance microsupercapacitors. The low areal energy density of microsupercapacitors with the interdigitated architecture is the major challenge hindering the application. Here, a simple method for the scalable fabrication of all‐solid‐state, flexible microsupercapacitors is demonstrated by direct graphene‐carbon nanotube composite ink writing technology. The microsupercapacitors demonstrate good electrochemical performance with a high areal energy density of 1.36 µWh cm –2 and power density of 0.25 mW cm –2, good cycling stability, and excellent mechanical flexibility. The method developed here sheds light on the simple method of preparing high‐performance, all‐solid‐state, flexible microsupercapacitors in a straightforward and scalable process. Abstract : A solution‐processed graphene‐carbon nanotube composite ink is developed for scalable writing all‐solid‐state, flexible microsupercapacitors devices. The devices demonstrate high areal capacitance, high areal energy density and power density, and good cycling stability with excellent mechanical flexibility.